Judicial Review of the Application of Corporate Legal Veil in Malaysia and Indonesia: A Legal Comparison - Zilmi Haridhi; Adam Afiz; Samuel Buha Raja Nadeak; Muhammad Fadil; Muhammad Hakeem (Recht Studiosum Law Review, 2024)
This study aims to find a comparison of the Legal Corporate Veil between Malaysia and Indonesia. This research is a normative legal research as a literature review. It is found that in corporate law both in Malaysia and Indonesia there is a principle of limited liability between shareholders and company directors known as Separate Legal Entity. This principle essentially asserts that a person's responsibility in a company is limited to their responsibility within the company and does not extend to personal liability. In Malaysia, this regulation is governed by Section 20 of the Companies Act 2016. Meanwhile, in Indonesia, this principle is scattered in the provisions of the Limited Liability Company Act (UU PT) applicable to shareholders, directors, and commissioners. However, this principle may become inapplicable in certain cases, known as Piercing The Corporate Veil. In Malaysia, this is regulated under the Companies Act 2016 as well as several judicial decisions. In Indonesia, this principle becomes inapplicable if shareholders act in bad faith by using the company for personal gain and are involved in legal actions undertaken by the Company. One form of protection from personal liability for Directors and Commissioners is implemented based on the Business Judgement Rule principle. Personal liability does not apply if Directors and Commissioners can prove that the company's loss is not due to their negligence, they have acted in good faith, have no conflict of interest, and have taken action to prevent losses. In this study, there is also corporate responsibility outside the existing Limited Liability Company Law based on business and economic developments decided by The Constitutional Court.